Ageism, empathy, attitudes, and aging anxiety: an evaluation of the Gray for a Day program with college students - Goss, Kaylee (Kansas State University, 2020)
Studies have shown ageism, empathy, attitudes toward older adults and aging anxiety to be important factors for not only individuals planning to work with older adults, but for all individuals to be able to age healthfully. Increased levels of empathy are associated with decreased levels of ageism and knowledge of the aging process promotes more positive attitudes towards aging and decreased aging anxiety. Aging simulations have been created to increase empathy, improve attitudes toward older adults, and decrease ageism and aging anxiety, but there are still mixed results when evaluating these programs. This study utilized Kolb’s experiential learning theory to understand the ways in which participation in the Gray for a Day program, an educational program about sensory and functional decline in older adults, impacts ageism, empathy, attitudes toward older adults and aging anxiety by evaluating the Gray for a Day program with students in an introduction to human development course at a Midwestern university. Changes in ageism, empathy, attitudes toward older adults and aging anxiety after participation in Gray for a Day were assessed using paired samples t-tests. Results showed that participation in Gray for a Day significantly increased positive attitudes towards older adults and the level of understanding and positive perceptions of older adult experiences among participants. Other measures showed decreases in ageism, empathy, and aging anxiety following participation in the program, but the differences were not statistically significant. Results indicate that the Gray for a Day program is effective at improving attitudes toward older adults and increasing understanding and positive perceptions of older adult experiences, but further evaluation and possible program adjustments are needed to reassess for ageism, empathy, and aging anxiety outcomes from the program.
Keywords: Program evaluation; Aging simulation; Ageism; Empathy; Attitudes toward older adults; Aging anxiety